Biologically oriented synthesis of medicines (BIODS) based on heterylpoxid 2,5-disubstituted 1,3,4-oxadiazoles (Part 2) - Yu. V. Karpenko; S. M. Kulish; N. А. Al Halaf (Zaporozhye State Medical University, 2021)
Heterocyclic compounds make a very important branch of organic chemistry, and it has always been an interesting area of study in medical chemistry. They are present in a variety of drugs, vitamins and biologically active compounds. Over two decades, 1,3,4-oxadiazoles have been of interest to chemists owing to their diverse therapeutic potential; the studies focus mainly on the principles of combinatorial chemistry with a broad spectrum of biological activity. In the continuation of the review article, the general literature sources that consider chemical heteryl derivatives of 2,5-disubstituted 1,3,4-oxadiazoles as important synthetic substrates and precursors for biologically oriented synthesis, are systematized. Heterocyclic 1,3,4-oxadiazoles and their derivatives are widely used as antibacterial, fungicidal, anti-inflammatory, antidiabetic, anticancer, antitubercular, antioxidant, antimalarial, analgesic, anticonvulsant, antidepressant and anti-HIV drugs. It is important to note that the combination of 1,3,4-oxadiazole nuclei with different heterocyclic moieties in some cases had synergistic effect. The aim of the work is the search for new activities, systematization and generalization of literature sources on methods of biologically oriented drug synthesis (BIODS) based on heteryl derivatives of 2,5-disubstituted 1,3,4-oxadiazoles. Conclusions. The article analyzes, generalizes and systematizes the data obtained from the literature that describes the results of the study of the biological activity of 1,3,4-oxadiazoles, which allowed to confirm their diverse pharmacological and biological potential. It is established that oxadiazoscafold as the main structural component is found in various biologically active compounds which evidences the relevance of its further studies as a perspective structural matrix for construction of drug-like molecules. The analysis of the presented material demonstrates the significance and prospectivity of biologically oriented drugs of this segment of the chemistry of nitrogen-containing heterocycles.